Understanding the coexistence of competing raptors by Markov chain analysis enhances conservation of vulnerable species - SARA', Maurizio; Mascara, R; Lopez Lopez, PM (Journal of Zoology, 2016)
Understanding ecological interactions among protected species is crucial for correct management to avoid conflicting outcomes of conservation planning. The occurrence of a superior competitor may drive the exclusion of a subordinate contestant, as in Sicily where the largest European population of the lanner falcon is declining because of potentially competing with the peregrine falcon. We measured the coexistence of these two ecologically equivalent species through null models and randomization algorithms on body sizes and ecological niche traits. Lanners and peregrines are morphologically very similar (Hutchinson ratios <1.3) and show 99% diet overlap, and both of these results predict competitive exclusion. In contrast, their use of diverse cliff substrates for breeding in different times of the season would predict coexistence. To compare these two mutually excluding hypotheses, we examined the pattern of inter-specific transitions in 88 sites that were studied for 14 years (2000–2013) using a Markov chain (MC) occupancy state model, and checked the sensitivity and elasticity of the community structure to changes in transition probabilities. During the study period, 1144 territorial transitions occurred in peregrine and lanner territories, and the MCs were predicted to converge to a stable equilibrium in 2065. Markovian analysis suggested that temporal and spatial segregation of habitat during reproduction might prevail over anatomical specialization for hunting and diet, allowing species coexistence, despite the prediction that peregrines will outnumber the lanners in future projections. Our approach combining niche-overlap analysis and species occupancy modelling led to practical information about conservation options available for the threatened lanner. Lanners are very sensitive to site abandonment, and measures increasing adult persistence in occupied territories could be more rewarding than those encouraging juvenile dispersal and colonization of new sites.